Prioritizing novel and existing ambulance performance measures through expert and lay consensus: A three‐stage multimethod consensus study - Coster, Joanne E. (Health Expect, 2017)
BACKGROUND: Current ambulance quality and performance measures, such as response times, do not reflect the wider scope of care that services now provide. Using a three‐stage consensus process, we aimed to identify new ways of measuring ambulance service quality and performance that represent service provider and public perspectives. DESIGN: A multistakeholder consensus event, modified Delphi study, and patient and public consensus workshop. SETTING AND PARTICIPANTS: Representatives from ambulance services, patient and public involvement (PPI) groups, emergency care clinical academics, commissioners and policymakers. RESULTS: Nine measures/principles were highly prioritized by >75% of consensus event participants, including measures relating to pain, patient experience, accuracy of dispatch decisions and patient safety. Twenty experts participated in two Delphi rounds to further refine and prioritize measures; 20 measures in three domains scored ≥8/9, indicating good consensus, including proportion of calls correctly prioritized, time to definitive care and measures related to pain. Eighteen patient/public representatives attended a consensus workshop, and six measures were identified as important. These include time to definitive care, response time, reduction in pain scores, calls correctly prioritized to appropriate levels of response and survival to hospital discharge for treatable emergency conditions. CONCLUSIONS: Using consensus methods, we identified a shortlist of ambulance outcome and performance measures that are important to ambulance clinicians and service providers, service users, commissioners, and clinical academics, reflecting current pre‐hospital ambulance care and services. The measures can potentially be used to assess pre‐hospital quality or performance over time, with most calculated using routinely available data.